THE EFFECT OF ORGANIZATIONAL COMMITMENT AND WORK STRESS ON EMPLOYEE JOB SATISFACTION IN PT. SARI MURNI PRATAMA MEDAN - Situpang, Ardi (Cattleya Darmaya Fortuna, 2025)
From the initial research that researchers did, many things canaffect employee job satisfaction, for that the company must striveto ensure that the factors related to employee job satisfactioncan be fulfilled optimally such as how to increase organizationalcommitment and work stress can be applied optimally byemployees within the company. This also depends on the qualityof human resources that exist within the company, whether it willbe able to fulfill if organizational commitment and work stress asan element that influences employee job satisfaction can becreated perfectly. The purpose of this study was to determineand analyze the influence of organizational commitment andwork stress on employee job satisfaction at PT. Sari MurniPratama Medan. The number of samples in this study amountedto 37 people using saturated sample techniques. The analysistechnique used is multiple linearregression. The results showthat organizational commitment does not significantly affectemployee job satisfaction. From the results of regression testsobtained the results of the study that work stress significantlyaffects employee job satisfaction. Together the variables oforganizational commitment and work stress have a significanteffect simultaneously on employee job satisfaction. With this itcan be concluded that the hypothesis of this study can beproven